Studies on Clostridium acetobutylicum P262 : sporulation induction and analysis of an oligosporogenous, solvent-deficient mutant - Babb, Brendan Lloyd (Department of Molecular and Cell Biology, 2016)
The ability of various fermentation products to induce sporulation was in order to design a sporulation induction medium for Clostridium acetobutylicum P262. Of acetic acid, butyric acetone and butanol, was found to be most effective at induction. Induction was more efficient at low pH values under certain conditions. The heat resistance of mature spores was determined and the optlmal temperature for spore quantification was shown to be 75·C. acetobutylicum mutants m5 06 were by transposon mutagenesis using the conjugative transposon Tn925::Tn917, not transposon Tn925 as previously thought [Babb. B.L. 1990. B.Sc. (Honours) thesis, University of Cape Town. South Africa]. The spore development and the fermentation profiles of mutants were in batch over a period of 60h. Mutant m5 was shown to be oligosporogenous with majority of cells blocked at sporulation stage H. It was deficient in acetone and butanol production. Mutant 06 proceeded to sporulation stage VII and produced acetone and butanol at levels similar to that of the wild type strain. Mutants 06 appeared to contain two respectively from Southern hybridization experiments using a probe for left transposon junction. However, when a probe to right transposon junction was used, the chromosomal deoxyribonucleic acid (DNA) of mutant m5 was shown to contain approximately eight junction sites. The cause for the anomalous hybridization pattern was non-specific restriction enzyme activity nor a result of independent transposition of transposon Tn917.